Respect, pluralism, and justice : Kantian perspectives - Hill, Thomas E. (Oxford University Press, 2000)
This is a collection of essays that interpret, examine critically, and extend Kant's moral and political thought on several important topics. The aim is to understand Kant, to address serious objections to his positions, and to explore ways in which contemporary Kantian theory can be fruitfully developed.